Evolution of Global Terrestrial Gross Primary Productivity Trend - Zihao Wang; Josep Peñuelas; Torbern Tagesson; W. K. Smith; Mousong Wu; Wei He; Stephen Sitch; Songhan Wang (Ecosystem Health and Sustainability)
Increased global vegetation gross primary productivity (GPP) over the past decades has led to an enhanced terrestrial carbon sink, an important factor in mitigating global warming. However, the global spatiotemporal evolution of GPP trends is still under debate, largely limiting our understanding of the sustainability in terrestrial carbon sink. Here in this study, based on a dozen of long-term global GPP datasets, we found that global GPP trends fell significantly from 0.43 PgC year−2 in 1982–1999 to 0.17 PgC year−2 in 2000–2016, a signal detected across >68% of the terrestrial surface. The decrease in GPP trends was more pronounced from satellite-based GPP datasets than from process-based models, which may result from a decline in the CO2 fertilization effect. This finding therefore indicates that the terrestrial carbon sink may become saturated in the future, and highlights the urgent need of stricter strategies for reducing carbon emissions to mitigate global warming.